Pretty deadly (2013), volume 3 ebook The rat. - DeConnick, Kelly Sue (Pretty Deadly (2013), 2020)
The Eisner-nominated, New York Times bestselling world of PRETTY DEADLY returns, this time to the sun-soaked strips of ‘30s-era Hollywood. Here, the best and brightest are dimmed and broken and the granddaughter of Sara Fields is found dead. Desperate to solve her murder, her heartbroken uncle calls on the Reaper of Vengeance to aid him. Collects PRETTY DEADLY: THE RAT #1-5. “Grand and majestic storytelling.” —Warren Ellis. “Cherish it." —Kieron Gillen. “A masterpiece of mythopoeism." —N.K. Jemisin, NYT Book Review. “Pushes the boundaries of comics storytelling in the most wicked ways. I love it.” —Ed Brubaker. “Sergio Leone crossed with Neil Gaiman’s American Gods.” —Tor.com. Author: Kelly Sue DeConnick. Illustrator: Emma Ríos. 2020 Milkfed Criminal Masterminds, Inc. and Emma Ríos.